Pengaruh Persepsi Kegunaan, Persepsi Kemudahan Penggunaan, Persepsi Keamanan Web, dan Informasi Online Banking Terhadap Minat Individu Menggunakan Internet Banking - Yogastyan Arizona (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
The Influence Perception usefulness, Perceived Ease of Use, Perceived Web Security and Online Banking Information on The Interests of Individuals Using Internet Banking. The purpose of this study was to examine the factors that affect the interests of individuals using internet banking which are perceived usefulness, perceived ease of use, perceived web security and online banking information using a modification Technology Acceptance Model (TAM). This research was conducted in three state-owned banks, namely Mandiri, BNI and BRI located in the town of Sidoarjo by using the survey method. Researchers obtained a sample of 200 customers of Bank Mandiri, BNI and BRI in Sidoarjo who use internet banking which were then processed using Partial Least Square (PLS) to examine the obtained research data. Results of the analysis for this model indicate that constructed perception of usefulness, perceived ease of use, perceived web security and online banking information strongly influence interest in the use of internet banking. It can be concluded that the interest in using internet banking can be influenced by perceptions of usefulness, perceived ease of use, web security perception, and online banking information. The implications of this study are relevant for the management of the bank to pay attention to returned usability factor, ease of use, web security, and information about online banking in implementing and developing the internet banking system and attracting more customer. ABSTRAK: Pengaruh Persepsi Kegunaan, Persepsi Kemudahan Penggunaan, Persepsi Keamanan Web, dan Informasi Online Banking Terhadap Minat Individu Menggunakan Internet Banking.